CASE REPORT OF LEBER HEREDITARY OPTIC NEUROPATHY - Полукарова, Елена Алексеевна; Волкова, Александра Константиновна; Байдалина, Елена Витальевна; Берг, Алина Константиновна; Соколов, Сергей Валентинович (Medicine in Kuzbass, 2023)
Objective – the clinical observation of sporadic genetic confirmation of a case of neuropathy.Methods. There was an analysis of the patient's medical history (anamnesis data, laboratory, instrumental (MRI, OCT, perimetry, ophthalmoscopy) and genetic studies), admitted to the neurological department of NGKB N 1 with unspecified atrophy of the optic nerves.Results. Detailed neuro-ophthalmological examination was performed during hospitalization. Other possible causes of visual impairment were excluded. It was suggested that the patient may have Leber's disease. Patient was sent for genetic testing, which revealed the m/11778G>A mutation in the homoplasmic state. Establishment of the diagnosis made it possible to adjust the therapy. The patient was discharged to the outpatient stage with positive dynamics.Conclusions. The present clinical observation illustrates that awareness of this pathology makes it possible to conduct a comprehensive examination, refer the patient for medical genetic counseling, establish a diagnosis in a timely manner, and prescribe pathogenetic treatment.
Keywords: optic neuropathy; Leber disease; mitochondrial disease; optic nerve atrophy; hereditary neuropathy; mutations; retinal ganglion cells